Modification trends of terraced houses: a case study of section 7, Shah Alam, Selangor / Salehaton H. Sazally … [et al.] - Sazally, Salehaton H.; Omar, Erdayu 0s’hara; Hamdan, Hazlina; Ibrahim Bajunid, Anniz Fazli (Universiti Teknologi MARA Cawangan Selangor, 2016)
Terraced or link houses have been one of the most popular housing schemes lived by modern Malaysians from all walks of life due to its design and affordability amongst all landed properties. Conversely, the mass housing production concept has its disadvantages and in most cases could not complement to the diverse individual needs and personal satisfaction of personalisation. The most distinctive evidence is the adhered normal practice to renovate or modify houses even as early as when the owner is given vacant possession of the property. Users make changes for various reasons such as for personal needs, functional requirements or just plainly for aesthetic appeal. Housing modification or occurs when users modify the interior or exterior physical components of their homes. Modification works ranges from a simple change of colour of the facade to major structural changes to the home. It is also much based on individual affordability and the timing J{Jr the modifications to be made. A questionnaire survey was conducted in a terraced housing development in Section 7, Shah Alam, Selangor, to establish the personalisation trends and the motivational desires behind the personalisation.